Dexterity, activity performance, disability, quality of life, and independence in upper limb Veteran prosthesis users: a normative study. Issue 11 (22nd May 2022) - Resnik, Linda; Borgia, Matthew; Cancio, Jill; Heckman, Jeffrey; Highsmith, Jason; Levy, Charles; Phillips, Samuel; Webster, Joseph
Abstract: Purpose: To present population data on standardized measures of dexterity, activity performance, disability, health-related quality of life (HRQoL) and community integration for persons with upper limb amputation (ULA), compare outcomes to normative values, and examine differences by prosthesis type and laterality (unilateral vs. bilateral amputation). Materials and methods: Multi-site, cross-sectional design, with in-person evaluations, functional performance, and self-report measures. Descriptive and comparative analyses were performed by amputation level and prosthesis type, data were compared for unilateral and bilateral amputation. Results: One hundred and twenty-seven individuals participated; mean age 57 years, 59% percent body-powered prostheses users. All measures of dexterity differed ( p < 0.05) by amputation level and by laterality. All measures of activity differed by amputation level with the best scores in transradial (TR) amputation groups. Comparisons of body-powered users with TR amputation found that dexterity was better for those with bilateral compared to unilateral amputation. Conclusions: Dexterity is markedly impaired in persons with ULA. Individuals with more proximal ULA levels are most impacted. HRQoL and community participation are less impacted and more equivalent to unimpaired persons. Further research is needed to examine differences by terminal device type and determine how best to match persons with ULA to the optimal prosthesis type and componentry, based on individual characteristics. Implications for Rehabilitation: This study provides population-based, comparative data on dexterity, activity performance, disability, quality of life, and independence in upper limb prosthesis users. The study provides preliminary analyses comparing the effectiveness of body-powered devices, myoelectric devices with single degree of freedom and multi-degree of freedom terminal devices. The data presented in this study can be used to benchmark outcomes in patients who are upper limb prosthesis users. The data will also be useful to inform comparative evaluations of existing and emerging prosthetic technology.